RARE-28. HYPOTHALAMIC GERMINOMA AND NEUROSARCOIDOSIS: A TALE OF TWO PATHOLOGIES. (11th November 2019) - Puri, Sushant; Valy-Nagy, Tibor; Sweiss, Nadera; Maraka, Stefania; Nicholas, Martin
Abstract: CASE 1: 30-year-old Caucasian male with a history of hereditary cavernomas, testicular germ cell tumor s/p orchiectomy 2017 presented next year with a chief complain of increasing lethargy. MRI Brain showed a new expansile, homogenously enhancing hypothalamic lesion causing obstructive dilatation of the lateral ventricles. MRI of neuraxis was not concerning for leptomeningeal spread. Initial differentials included suprasellar germinoma vs chiasmatic hypothalamic glioma vs metastatic lesion. Biopsies X2 showed gliosis and granulomatous inflammation. Despite radiation treatment for the hypothalamic mass clinical course continued to deteriorate. CSF results showed RBC - 1, 200; WBC - 51 with 77% lymphocytes, 3% neutrophils, 20% monocytes. FDG-PET did not reveal evidence of metastatic disease. He was treated presumptively for neurosarcoidosis with high-dose corticosteroids and azathioprine and later transitioned to methotrexate and infliximab. Follow up MRI scans showed a reduction in the hypothalamic mass. CASE 2: A 23-year-old African American male treated for ADEM in 2010 presented to clinic with behavioral problems in 2017. Initial presentation included lethargy with imaging showing an incidental hypothalamic mass. Initial differentials included germinoma vs infundibular hypophysitis vs granulomatous process. He was treated with immunotherapy (corticosteroids and IVIG) with partial resolution of the growth. He was later diagnosed with suprasellar germinoma on biopsy subsequently treated with 2 cycles chemotherapy and proton beam radiotherapy in 2012. In 2017. to exclude tumor recurrence an LP showed elevated ACE however remainder of the clinical picture was not suggestive of neurosarcoidosis. DISCUSSION: Multiple case series have been described wherein hypothalamic germinoma mimics isolated neurosarcoidosis and vice-versa. Because of similar clinical picture and radiographic findings, the diagnosis is challenging. ACE is a nonspecific test for neurosarcoidosis, and it can be positive in the setting of germinoma as well. Hence specific molecular markers may be helpful in the diagnosis.